Isolation, Identification, and Function of Rhodotorula mucilaginosa TZR2014 and Its Effects on the Growth and Health of Weaned Piglets - Hu, Ping; Mao, Junxia; Zeng, Yan; Sun, Zhihong; Deng, Huan; Chen, Chen; Sun, Weizhong; Tang, Zhiru (Frontiers in Microbiology, 2022)
A red yeast isolated from orange and grape soil and identified by the 26S rDNA sequence analysis revealed that it was R. mucilaginosa and named TZR2014. Its biomass and carotenoid production reached a maximum when using the fermentation medium with pH 6.0, containing 5% glucose, 1% peptone, and 1.5% yeast powder. TZR2014 was resistant to 55 °C for 15 min, 0.2% pig bile salts for 4 h, and artificial gastric and intestinal fluids. Thirty 28-d weaned pigs were divided into three groups and the piglets were fed a basal diet (CON), a basal diet and orally administered 1 mL 1.0 × 1010 CFU/mL Candida utilis DSM 2361 three times (C. utilis), or a basal diet and thrice daily orally administered 1 mL 1.0 × 1010 CFU/mL TZR2014 (R. mucilaginosa) for 4 weeks. Compared with the piglets in the CON group, those in the C. utilis or R. mucilaginosa group reported an increased average daily weight gain and average daily feed intake (P < 0.05) and decreased feed/gain (P < 0.05). The diarrhoea rate of piglets in the R. mucilaginosa group was lower than that in the CON and C. utilis groups (P < 0.05). Compared with that in the CON and C. utilis groups, the R. mucilaginosa group reported an increased ileum villus height (P < 0.05); serum concentration of total antioxidant content, total superoxide dismutase, and glutathione peroxidase and pepsin and lipase activity in the intestinal content, while decreased serum concentration of malondialdehyde and pH of the intestinal tract (P < 0.05). The relative abundances of Proteobacteria and Megasphaera of caecum in the R. mucilaginosa group were lower than those in the CON and C. utilis groups (P < 0.05). The relative abundances of Prevotella, Ruminococcaceae, Succinivibrio, Rikenellaceae RC9 gut group, and Roseburia of caecum in the R. mucilaginosa group were higher than those in the CON and C. utilis groups (P<0.05). TZR2014 can produce carotenoids and adapts to the animal gastrointestinal environment. Oral TZR2014 improved growth performance, enhanced antioxidant capacity, strengthened gastrointestinal digestion and maintained the intestinal microbiological balance of piglets.